The Rise of Multidrug-Resistant Bacteria in Hospitals: Investigating Sources, Spread, and Strategies for Control - Mahmood, Mohammed Mahmood Hameed; Fadel, Sajad Firas Abd; Ali, Haneen Ali Abdul Hussein Abdul; Wahed, Ali Mahmood Shaker; Faraj, Nagham Ali Issa (American Journal of Botany and Bioengineering, 2025)
Multidrug resistant (MDR) bacteria are an ever-growing concern worldwide, particularly for hospitalised patients. These organisms remain a persistent source of healthcare associated infections (HAIs) and have become a critical threat, with only limited treatment options currently available. As a result, the risk to patient safety and well-being has been intensified, with increased hospital stays and mortality rates. It is essential, therefore, to understand the origins of MDR bacteria in hospital settings, the mechanisms and routes through which they spread, and the methods by which the dissemination of these organisms can be effectively controlled. Several factors contribute to the increased risk of MDR bacterial infection in hospitals: Indwelling medical devices act as key pathways for infection; the use, and frequently overuse, of antimicrobial agents creates selective pressure which enables bacteria to develop resistance; and the spread of MDR bacteria is, of course, facilitated by cross-transmission within the healthcare environment. Bacteria are capable of several different mechanisms of resistance, spanning efflux pumps and decreased permeability through enzymatic inactivation and alteration of the target structure. Such mechanisms may be employed individually or in combination to build the phenomenon of multi-drug resistance. MDR can be understood as resistance to three or more classes of antimicrobial agents. These mechanisms arise naturally within the population but are encouraged through selective pressure, such as lack of adherence to antibiotic treatment and the overuse of antimicrobials, which can lead to the development of MDR bacteria and their rapid proliferation in both hospitals and the community.